2018
DOI: 10.3389/fendo.2018.00454
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Levothyroxine on Blood Pressure in Patients With Subclinical Hypothyroidism: A Systematic Review and Meta-Analysis

Abstract: Background: Patients with subclinical hypothyroidism (SCH) have elevated blood pressure, but the effect of levothyroxine (LT4) therapy on blood pressure among those patients is still unclear. This study aimed to assess whether LT4 therapy could reduce blood pressure in SCH patients through a systematic review and meta-analysis.Methods: PubMed, Embase, Cochrane Central Register of Controlled Trials (CENTRAL), and Web of Science were searched. Randomized controlled trials (RCTs) assessing the effect of LT4 thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 90 publications
2
7
0
Order By: Relevance
“…The relation between subclinical hypothyroidism and hypertension has always been a controversial issue [ 9 ]. The previous meta-analyses have also reported inconsistent results on this matter [ 24 ]. Previous research disputes have focused on the level of office blood pressure [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relation between subclinical hypothyroidism and hypertension has always been a controversial issue [ 9 ]. The previous meta-analyses have also reported inconsistent results on this matter [ 24 ]. Previous research disputes have focused on the level of office blood pressure [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…So it suggested that post-pregnancy treatment may reduce the chance for LT4 to have a beneficial effect. And the latest meta-analysis shows that LT4 replacement therapy can reduce blood pressure in SCH patients (29). But to date, the universal screening for thyroid function in childbearing women has been much debated in the scientific literature (6).…”
Section: Discussionmentioning
confidence: 99%
“…Only longitudinal studies can confirm this hypothesis and establish whether a substitutive treatment with levothyroxine is really needed in these patients [31]. A recent systematic review suggests that levothyroxine replacement therapy can reduce blood pressure in adults with SCH but the results need to be validated in more clinical trials with larger samples [32]. Similar trials are also needed in obese children with IsHT.…”
Section: Discussionmentioning
confidence: 99%